Knowledge structure and theme trends analysis on general practitioner research: A Co-word perspective - Hong, Yang (BMC Fam Pract, 2016)
BACKGROUND: General practitioners (GPs) are the most important providers of primary health care, as proven by related research published several decades ago. However, the knowledge structure and theme trends of such research remain unclear. Accordingly, this study aimed to provide an overview of the development of research on GPs over the period of 1999 to 2014. METHODS: Studies on GPs conducted from 1999 to 2014 were retrieved from PubMed. In this work, co-word, social network analysis, and theme trends analyses were conducted to reveal the knowledge structures and thematic evolution of research on GPs. RESULTS: The number of conducted studies on GPs increased. However, growth speed slowed down during the past 16 years. A total of 27 high-frequency keywords were identified in 1999 to 2003, and more new and specific high-frequency keywords emerged in the subsequent periods. The dynamic of this field was first divergent and then considered convergent. Specifically, network centralization is 19.77 %, 19.09 %, and 13.04 % in 1999 to 2003, 2004 to 2008 and 2009 to 2014, respectively. The major topics of research on GPs completed from 1999 to 2014 were “physician/family,”“attitude of health personnel,” and “primary health care,” and “general practitioner” communities, and so on. CONCLUSION: The research themes on GPs are relatively stable at the beginning of the 21(st) century. However, the thematic evolution and research topics of research on GPs are changing dynamically in recent years. Themes related to the roles and competencies of GPs, and the relations between general practitioner and patients/others have become research foci on GPs. In addition, more substantial research especially on comprehensive approaches and holistic modeling, which have been defined in the European Definition of General Practice/Family Medicine, are expected to be accomplished.